Visualization of fluid flow pathways in wood by low-field 1H and 3He contrast MRI. (June 2015) - Suchanek, M.; Olejniczak, Z.
Highlights: The low-field MRI experiment for visualizing water flow in wood was designed. The MR images illustrated the penetration of water in various types of wood. The flow occurs at the speed exceeding the diffusive moisture transport. The method for observing the hyperpolarized 3 He gas transport in wood was demonstrated. Abstract: A low-field Magnetic Resonance Imaging (MRI) technique was used for noninvasive studies of the internal structure of three types of wood, using water and 3 He gas as contrast agents. In the conditions of steady state water flow through the sample, the fluid flow pathways were found to be mainly located in the late wood. A substantial increase in sensitivity, or equivalently, a decrease in experiment time was demonstrated, when the hyperpolarized 3 He gas was used. The method opens new opportunities of studying a wide range of similar biologically permeable materials in a nondestructive way.